Pengenalan Energi Baru Terbarukan melalui Media Pembelajaran Interaktif pada Tingkat Pendidikan Dasar - Chairat, Arief Suardi Nur; Ridwan, Muhammad; Prayudi, Prayudi; Sany, Nasril; Dody, Dody; Kusumastuti, Dyah Pratiwi; Vaza, Hery; Asnul, Nur Shania (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Global warming has become a major concern due to its impacts on the environment and human life. One way to reduce these impacts is by increasing the use of renewable energy. Introducing the concept of renewable energy at the elementary school level is expected to foster students’ awareness and understanding of the importance of using clean energy. This Community Service (PkM) program aims to enhance the knowledge and understanding of students and teachers at SD Islam Al Azhar 5, West Jakarta, regarding solar-based renewable energy through an interactive learning approach. The activities were carried out in several stages, including survey, socialization, training, evaluation, and sustainability. The socialization session was delivered through material presentations supported by engaging visual media, while the training involved assembling toys powered by solar energy. The results showed strong enthusiasm, improved understanding of renewable energy among students and teachers, and enhanced teacher skills in implementing interactive learning. This program also encouraged greater awareness of the importance of adopting renewable energy in daily life.